(3eHGOF GdeMGSHI (B:s (3GdLRA GdChd (B/s - (3TbQ, YGeQs; (3GdTfWj, Gjef s ((3YeGf(B: s (3GdHOGjI(B, s, 2005)
(3LQO GdGUhd GdKGHJI , GdGUhd GdeJOGhdI , GdMSGHGJ GdhgejI h GdNUhe GdeJOGhdI , CKQ GdJShjGJ GdLQOjI Ydi bGFeI GdONd h GdeQcR GdeGdj , GdOaGJQ GdeSGYOI h GdWQb GdeMGSHjI h GdMSGHGJ GdeGdjI (B.s
Keywords: (3GdeMGSHIs; (3JObjb GdMSGHGJs